100 Significant Pre-Independence Speeches, 1858-1947 - Complied and Edited by Sharma, H. D. (New Delhi Rupa & Co., 2007)
Speeches by statesmen, politicians, revolutionaries, reformers, and bureaucrats of India and Britain
Include Bibliography
Keywords: India -- British Occupation of India (1765-1947) -- Politics and government